2006
DOI: 10.1007/s00198-006-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to osteoporosis treatment in clinical practice

Abstract: The results of this large survey of Italian osteoporotic women indicates that the most important determinant of both persistence and compliance to treatment is the type of drug prescribed with a definite advantage of ALN-OW. Treatment compliance is particularly poor for CaVitD and this emphasizes the need for new ways to supplement at least vitamin D. The main reasons for discontinuation are side effects and lack of motivation while the best treatment adherence was observed in patients with severe and well doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 25 publications
6
133
1
8
Order By: Relevance
“…Classically, it has been reported that patients affected by osteoporosis, in general, complied poorly with treatment, both with anti-resorptive drugs 7,8, , especially the bisphosphonates 12,13 , and with the anabolics 25 , and in a more fundamental way, with calcium and vitamin D supplements 26,27 . In some series it has been reported that the first thing that patients stop taking correctly is precisely calcium and vitamin D 28 , which is exactly the opposite to what we found in our study, where 84.1% of the fractured patients took calcium and vitamin D, while only 75.9% took any other drug.…”
Section: Discussioncontrasting
confidence: 99%
“…Classically, it has been reported that patients affected by osteoporosis, in general, complied poorly with treatment, both with anti-resorptive drugs 7,8, , especially the bisphosphonates 12,13 , and with the anabolics 25 , and in a more fundamental way, with calcium and vitamin D supplements 26,27 . In some series it has been reported that the first thing that patients stop taking correctly is precisely calcium and vitamin D 28 , which is exactly the opposite to what we found in our study, where 84.1% of the fractured patients took calcium and vitamin D, while only 75.9% took any other drug.…”
Section: Discussioncontrasting
confidence: 99%
“…This may appear shocking at first sight because in all the therapeutic guides and recommendations of professional organisations for the treatment of osteoporosis it is widely known and recommended that an adequate supply of calcium and vitamin D is the basis, and should always be associated with, treatment with osteoactive drugs for osteoporosis 48 . The high prevalence of women with vitamin D insufficiency, despite being subject to treatment, could be an indication of a potential absence of compliance 49 . Another possibility may be that the genetic makeup of our patients conditions for lower levels of vitamin D 50 .…”
Section: Impact On Bonementioning
confidence: 99%
“…[10] Determinants of poor adherence include inconvenient regimens, adverse effects and lack of motivation. [11,12] Denosumab represents a new therapeutic opportunity for the treatment of osteoporosis. The FREEDOM (Fracture REduction Evaluation of Denosumab in Osteoporosis every six Months) trial has recently shown subcutaneous administration of 60 mg of denosumab every 6 months to be well tolerated, to increase bone mineral density (BMD) and to significantly reduce the risks of vertebral, non-vertebral and hip fractures in women with osteoporosis over 3 years.…”
Section: Introductionmentioning
confidence: 99%